Empowering the Pakal Village Community in Improving Food Security with Hydroponic Planting - Kukuh Arisetyawan; Lustina Fajar Prastiwi; Ruth Eviana Hutabarat; Fahnur Ari Wijaya (Universitas Lancang Kuning, 2023)
This community service aims to help improve the community's food security by utilizing narrow land with hydroponic techniques. The land in the Pakal District, Surabaya City, is included in the narrow land caused by land use change. In addition, this community service provides real knowledge and skills on hydroponic planting procedures. The methods used are observation, discussion, simulation, and project-based mentoring. These simulations and mentoring activities consist of several activities, namely land cleaning, garden making, seedling cultivation, plant maintenance, and hydroponic plant harvesting. The results of the activities show that the program can be well implemented, as seen from the enthusiasm of the community to participate in opening the land and planting hydroponic plants from start to finish. The hydroponic land initially was neglected and poorly maintained. After this program, the previously neglected land was transformed into a beautiful garden, and the hydroponic land can be utilized by the surrounding community to grow vegetables or plants needed for daily life.